Preparation Of Activated Carbon From Mangrove Pile Leftover Via Physiochemical Activation - Ramli, Mohammad Fareez Adam (Universiti Sains Malaysia, 2017)
Activated production from mangrove pile leftover from solid waste from construction site is one of the most environment-friendly solutions by transforming waste to valuable product with high surface area. Thus, the main objective of this research was to prepare activated carbon from mangrove timber using two-step physiochemical activation method. The carbonization process was carried out at 600oC for 1 hour under nitrogen flow rate of 150 ml/min. After the carbonization process, the char were impregnated with potassium hydroxide (KOH) at different impregnation ratios (0.5, 1, 1.5). After the char were impregnated, the char were then proceed to activation process with the different activation temperature (750oC, 800oC and 850oC) for 1 hour.. The effect of different preparation of precursor on the activated carbon yield and adsorption capacity on methylene blue were investigated. The optimal activated carbon was found at activation temperature of 750oC with impregnation ratio 0.5, namely as AC 750(0.5).The metyhlene blue adsorption capacity is 243.90 mg/g. The experimental data of adsorption is well fitted to Temkin isotherm with a R2 value of 0.9909. The result of adsorption study showed that the activated carbon prepared from mangrove timber is suitable for methylene removal from aqueous soluti